Preliminary checklist of true mangrove species in Balok river Kuantan Pahang - Shamsuri, Nur Sharul l'zzati; Kamarudin, Mohd Shamin Shazwan; Che Amri, Che Nurul Aini; Mohd Yunus, Noor Syaheera; Zohari, Ahmad Fitri; Abdul Rahman, Mohamad Ruzi; Shahari, Rozilawati (Kulliyyah of Science, International Islamic University Malaysia, 2024)
This study aims to provide a preliminary checklist of true mangroves in the Balok river, Kuantan Pahang. Three samples were collected for each plant species. The plants collected fulfil the requirement of having roots, stems, leaves, flowers and fruit with no or minimal damage. These samples were pressed, dried, and affixed onto herbarium sheets and processed as herbarium vouchers by using the standard herbarium technique. These vouchers were then carefully catalogued and placed at, the Herbarium Department of Plant Science, International Islamic University Malaysia. Our research successfully identified and recorded a total of 16 true mangrove species where Rhizophora mucronata and Rhizophora apiculata were identified as common species. The findings from this study contribute significant potential for aiding future academic inquiries along with the conservation efforts of the Balok River mangrove ecosystem.